MINAT BELI KONSUMEN TOKO SEPATU BATA DIPASAR RAYA PADANG DILIHAT DARI SIKAP DAN IKLAN - Yuli Priyanti; Febsri Susanti; Nazaruddin Aziz (JURNAL PUNDI, 2017)
The company is engaged in the manufacture, import, export and distribution of leather shoes, built-up canvas, casual and sports shoes, injection slippers, and special shoes for industry. This study aimed to analyze the influence of each variable, the attitude (X1), advertising (X2) toward purchase intention. Data were collected through questionnaires. to 100 respondents Bata store consumer markets desert highway by using accidental sampling method to determine the respondents to each variable. By using the validity test, reliability test, descriptive analysis, multiple linear regression analysis, the coefficient of determination (R2), t-test, f. Data analysis technique used is multiple linear analysis. The result of this study shows that attitude and advertising have a significant effect on consumer buying interest in the purchase of shoes brick desert highway market.